MODEL PERNIKAHAN KOMUNITAS LEMBAGA DAKWAH ISLAM INDONESIA (STUDI KASUS DI KABUPATEN TULUNGAGUNG) - Krisna Fitriani Krisna Fitriani (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
This research is in the background of the marriage of fellow members of the Indonesian Islamic Da'wah Institute community which is a common thing for the Indonesian Islamic Da'wah Institute community. This is feared to affect the community because the community already knows about the practice of matchmaking in the Indonesian Islamic Da'wah Institute community up to the level of marriage. Many parties state that marriage between members of the Indonesian Islamic Da'wah Institute community and people who are not members of the Indonesian Islamic Da'wah Institute community (non-LDII) is not allowed because it is contrary to the hadith. In addition, local people, both inside and outside Tulungagung Regency, often express concerns about various marriage practices carried out by the Indonesian Islamic Da'wah Institute community. This research uses a qualitative research method (field research), specifically by seeking information in the field directly for interviews, observations, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawn. Analysis of the validity of the data which includes credibility and triangulation of data. The results of this study show that: (1) what is the tradition of marriage in the Indonesian Islamic Da'wah Institute community is: religious, social and community basis, marriage among the Indonesian Islamic Da'wah Institute community. (2) the model of marriage implementation in the Indonesian Islamic Da'wah Institute community is also divided into three points, namely: the process of finding a mate, the implementation of marriage and the prohibition of marriage in the Indonesian Islamic Da'wah Institute community. (3) The Analysis of the Compilation of Islamic Law is contained in article 61 and the Marriage Law No. 1 of 1974 is contained in article 2 paragraph 1. Both provide a legal framework that must be followed because there are several differences regarding the teachings of marriage in the Indonesian Islamic Da'wah Institute community in Tulungagung Regency.